Sustainable environmental governance as the implementation of state defense policy - Muslikhatin, Lilik; Supriyadi, Asep Adang (Journal of Placemaking and Streetscape Design, 2024)
Background: Land waters in urban areas often become a source of problems if they are not managed wisely and firmly. The threat and risk of danger, disease and even death always haunt the people who live on the banks of the river. Poverty and slum areas are negative effects of less than optimal land water management in urban areas. The Indonesian government has taken various steps to address this, but the lack of urban land for settlement is the reason why immigrants from other regions reside and reside in dangerous areas such as riverbanks. The compulsion to live minimally in urban areas is a burden for local governments in their efforts to increase welfare as well as improve sustainable urban governance. Many other cities in developed countries have made efforts to improve inland water areas to alleviate poverty and at the same time beautify the urban landscape. The experts agreed to hold discussions to formulate the best policy steps for sustainable urban governance in Indonesia. Methods: In the process of data analysis and decision making related to sustainable environmental governance as implementation of national defense policy, this article utilizes the Analytical Hierarchy Process (AHP) Data Processing Method. Finding: The results of in-depth discussions and interviews with experts in the field of environment, urban governance, economic experts and poverty management experts from various institutions such as the Ministry of Social Affairs, PUPR Ministry, Spatial Planning and City Planning Services, Academics and also the Military were processed using the Analytical Hierarchy Process (AHP). Conclusion: The best decision alternative will be a recommendation for policy makers regarding sustainable urban governance.  Novelty/Originality of this study: This study is relevant to the Analytical Hierarchy Process (AHP) Method to formulate sustainable urban water management policies in Indonesia, involving various experts and related institutions to overcome poverty and improve urban landscapes. Therefore, this study can show policy recommendations based on various aspects and views.